Perceptions and Satisfaction of Saudi Medical Students with Neurology Education: A National Exploratory Study - Raseel Abdulaziz Aljthalin; Raneem Abdulaziz Aljthalin; Arwa Suliman Aljagwani; Dareen Abdulelah Alanazi; Basel Abdullah Almeflh; Abdulrahman Obaid Alharbi (Dr. Sulaiman Al Habib Medical Journal)
Most medical students perceive neurology as a difficult subject. Therefore, this results in students developing neurophobia. This study aimed to provide a national data source on the perceptions and satisfaction of Saudi medical students with neurology education. In 2018, an exploratory cross-sectional study was conducted among 3rd to 6th year Saudi medical students (n = 409). The study encompassed 29 medical schools in the Kingdom of Saudi Arabia. The students were recruited using cluster sampling of all regions of the Kingdom. The data were analyzed using descriptive statistics and analysis of variance. Based on a five-point Likert scale, the students had modest perceptions (mean = 2.91 ± 0.78) and modest satisfaction levels (mean = 2.97 ± 1.02) with neurology education. There were no significant differences in perceptions or satisfaction by sex, nationality, or university type. Nevertheless, highly significant differences in both perceptions and satisfaction across universities were found (p = 0.000). In general, Saudi medical students suffer from neurophobia. Given the implication of neurology and brain health, a national strategy is needed to address medical students’ perceptions, knowledge, and skills with regard to neurology education. This is essential to promote career development needs among medical graduates, and to meet service demands for neurologists in Saudi Arabia. Furthermore, efforts are needed to align and reduce existing variations across medical schools in the Kingdom.